Channels of firm expansion and contraction - Holger Breinlich; Stefan Niemann (Verein für Socialpolitik, 2010)
We propose a model of firm expansion and contraction choices which integrates approaches from the industrial organization and corporate finance literature within one unified setting. Firms respond to shocks to their marginal costs by expanding or contracting output via internal or external adjustment. External adjustment can take place via greenfield investment or disinvestment and/or mergers and acquisitions (M&As). We show theoretically how the choice of adjustment strategy varies systematically with observable characteristics, in particular firm size and the magnitude of adjustment. We then test the model's predictions using novel business register data for the United Kingdom. In contrast to existing datasets, our data allow for a joint analysis of all three adjustment forms highlighted by the theory. The data are also not limited to publicly traded firms and cover almost the entire universe of UK firms, representing 99% of UK employment and turnover. We find broad support for the theoretical predictions of our model.
Keywords: E22; G31; G32; 330; Adjustment Channels; Mergers and Acquisitions; Greenfield Investment; Investment